AKTIVITAS SENYAWA FLAVANOID EKSTRAK ETANOL BUNGA KERSEN (Muntingia calabura L) SEBAGAI TABIR SURYA - Masdiana Tahir; Rahmawati Rahmawati; St Maryam; Putri Nurfauziah; Naura Nazhifah (As-Syifaa Jurnal Farmasi, 2022)
Chronic exposure to ultraviolet rays from the sun might result in oxidative stress, changes in the structure and composition of the skin. Sunscreen preparations are recommended to be used to prevent or minimize the harmful effects of UV rays on the skin. Sunscreen can be obtained from natural ingredients, one of which is the flower of cherry (Muntingia calabura L.). This study aims to identify the content of flavonoids and test the sunscreen activity of the ethanol extract of cherry flower (Muntingia calabura L.) in vitro using the UV-Vis spectrophotometric method based on the SPF value. Flavonoids are claimed to be capable to blocking ultraviolet (UV) light-induced radicals that have a protective effect against UV radiation, where the SPF value is a universal measure that describes the potency of a UV defense material. The findings of this study showed that the ethanol extract of cherry flowers positively contained flavonoid compounds including the flavonol, flavanone, and anthocyanidin groups. The results of the sunscreen activity test showed that the ethanol extract of cherry flowers had sunscreen activity at a concentration of 0.01% with an SPF value of 10.9 (moderate SPF), 0.05% with an SPF value of 41.6 (high SPF), 0,15% with an SPF value of 45.5 (high SPF). and 0.25% with an SPF value of 48.7 (high SPF). The higher the extract concentration, the higher the SPF value indicating the greater the activity as sunscreen.